Non-diabetic hypoglycaemia - P. Shah (Sri Lanka College of Internal Medicine, 2023)
Hypoglycaemia is diagnosed by the presence of symptoms of hypoglycaemia, documented low plasma glucose (often less than 50 mg/dl) at the time of symptoms, and recovery of symptoms by correction of glucose. If plasma glucose is normal at the time of symptoms, causes other than hypoglycaemia should be considered. If hypoglycaemia has been documented, the cause of hypoglycaemia should be investigated. Only after documentation of spontaneous endogenous insulin secretion causing hypoglycaemia should we proceed with localization of the tumor. Surgery will cure hypoglycaemia in about 90% of patients with insulinoma. Dumping syndrome can cause postprandial symptoms in people who have had upper gastrointestinal (GI) surgery (and rarely without surgery). The symptom complex in dumping syndrome includes the ones caused by GI stretching and GI hormones, or hypoglycaemia, or both. Dumping syndrome often needs to be managed by dietary interventions with or without pharmacotherapy.